The heart of everything that is eaudiobook The untold story of red cloud, an american legend. - Drury, Bob (Recorded Books Inc., 2014)
In the bestselling tradition of Empire of the Summer Moon, this is the untold story of Red Cloud, the most powerful Indian commander of the Plains who witnessed the opening of the West. The great Oglala Sioux chief Red Cloud was the only Plains Indian to defeat the United States Army in a war, forcing the American government to sue for peace in a conflict named for him. At the peak of their chief' s powers, the Sioux could claim control of one-fifth of the contiguous United States. But unlike Sitting Bull, Crazy Horse, or Geronimo, the fog of history has left Red Cloud strangely obscured. Now, thanks to painstaking research by two award-winning authors, his incredible story can finally be told. Born in 1821 in what is now Nebraska, Red Cloud grew up an orphan who overcame myriad social disadvantages to advance in Sioux culture. Through fearless raids against neighboring tribes, like the Crow and Pawnee, he acquired a reputation as the best leader of his fellow warriors, catapulting him into the Sioux elite— and preparing him for the epic struggle his nation would face with an expanding United States. Drawing on a wealth of evidence that includes Red Cloud' s 134-page autobiography, lost for nearly a hundred years, Bob Drury and Tom Clavin bring their subject to life again in a narrative that climaxes with Red Cloud' s War— a conflict whose massacres presaged the Little Bighorn and ensured Red Cloud' s place in the pantheon of Native American legends. A story as big as the West, with portraits of General William Tecumsah Sherman, explorer John Bozeman, mountain man Jim Bridger, Red Cloud protege Crazy Horse, and many others, The Heart of Everything That Is not only places you at the center of the conflict over western expansion, but finally gives our nation' s greatest Indian war leader the modern-day recognition he deserves.